1975
DOI: 10.1042/cs0480405
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Body Fat Content to Deep Muscle Temperature and Isometric Endurance in Man

Abstract: 1. The relationship between body fat content, isometric endurance and deep muscle temperature was assessed in eight male and female volunteers trained to static effort. 2. Muscle temperature, measured in the belly of the brachioradialis muscle, was found to be directly related to the subject's body fat content. 3. Associated with a reduction in body fat content, there was a marked decrease in deep muscle temperature and an increase in isometric endurance of the hand-grip muscles; no change in strength was note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 5 publications
0
22
0
1
Order By: Relevance
“…Further, in another study where female and male subjects participated in weight gain and weight loss programmes, it has been shown that the effect of body fat on isometric endurance for a contraction at a 40% MVC could be reversibly varied by simple weight loss and gain (Petrofsky and Lind 1975 a, b). The mechanism of this response was due to the insulative effect of body fat on the forearm muscle, causing resting muscle temperature to be higher and hence endurance lower in the overweight.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Further, in another study where female and male subjects participated in weight gain and weight loss programmes, it has been shown that the effect of body fat on isometric endurance for a contraction at a 40% MVC could be reversibly varied by simple weight loss and gain (Petrofsky and Lind 1975 a, b). The mechanism of this response was due to the insulative effect of body fat on the forearm muscle, causing resting muscle temperature to be higher and hence endurance lower in the overweight.…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that increased strength of contraction results in a greater occlusion of exercising blood flows and thereby limits endurance and in this study, the recovery of endurance. However, when subjects were matched for body fat, there was no significant correlation between strength and endurance (Petrofsky and Lind 1975 a, b). Further, it is generally agreed that contractions at a tension of 70% MVC of the handgrip muscles completely occlude the blood flow to the exercising muscles (Lind et al 1966).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Some texts recommend as few as six layers of towels [1,3] while other texts recommend nearly double this number of layers [2]. This is further complicated as heat transfer into the deep tissues is modulated by the thickness of the subcutaneous fat layer [12,13]. Body fat has a strong influence on skin and deep tissue temperature in man at rest [14].…”
Section: Introductionmentioning
confidence: 99%